(untitled) (Dimensión Empresarial, 2020)
Since the appearance of Covid-19, not only has the number of infections increased but also behaviors of an irrational nature and emotional blindness have been observed in developing countries. The objective of this research is to analyze this behavior in the decision-making process through qualitative research with an explanatory methodology and with a sample in Mexico. With the application of complex fractal system models (exact sciences), evolutionary maturity (biological sciences), and administrative theories (social sciences); It is concluded that Mexico is proactively facing the pandemic, which does not correspond to its economic reality.